Aldehyde dehydrogenase 1 (ALDH1) expression is an independent prognostic factor in triple negative breast cancer (TNBC). Issue 14 (April 2017) - Ma, Fei; Li, Huihui; Li, Yiqun; Ding, Xiaoyan; Wang, Haijuan; Fan, Ying; Lin, Chen; Qian, Haili; Xu, Binghe
Abstract : Abstract: Triple negative breast cancer (TNBC) is a subset of breast cancer that is highly aggressive and has a poor prognosis. Meanwhile, cancer stem cells (CSCs) are also characterized by a strong tumorigenic potential, which might be partly responsible for the aggressive behavior of TNBC. We previously showed that CSCs are enriched in TNBC cell lines and tissues. Further experiments in animal models revealed higher tumorigenicity of CSCs sorted from TNBC cell lines. In this study, we aimed to determine the clinical relationship between CSCs and TNBC by exploring the expression of aldehyde dehydrogenase 1 (ALDH1), which is a putative marker of breast CSCs, in TNBC tissues. ALDH1 levels in paraffin-embedded tumor tissues from 158 TNBC patients were evaluated by immunohistochemistry staining using an ALDH1A1 primary antibody. Staining evaluation was performed independently by two pathologists, and the expression level of ALDH1 was evaluated in terms of the percentage and intensity of positive cells. The association of immunohistochemistry staining of ALDH1 expression with clinical parameters was also analyzed. ALDH1 expression in tumor cells was observed in 88 out of 158 cases (55.7%). Analysis of clinicopathological parameters showed that the immunohistochemistry staining of ALDH1 was significantly correlated with tumor size ( P = 0.02) and stage ( P = 0.04). Survival analysis in patients with ALDH1 expression demonstrated shorter relapse-free survival (RFS) and overall survival (OS) times ( P = 0.01; P = 0.001). Moreover, Cox multivariate analysis revealed that ALDH1 expression was an independent prognostic indicator of RFS and OS ( P = 0.04; P = 0.04). Immunohistochemistry staining of ALDH1 in tumor cells is an independent prognostic indicator of RFS and OS in TNBC patients.